IMPACT OF THE UAE NATIONAL SERVICE ON ACADEMIC ACHIEVEMENT AMONG COLLEGE STUDENTS - Alhammadi, Fatima (2021)
The main focus of this study was to investigate the influence of the National Service programme in the UAE among the post-Secondary school Emirati youth on their academic development at higher learning institutions and hence career development in the future. To achieve this, three specific research objectives were developed to guide the study development. The first objective was to assess the experiential and learning skills taught at the national service that influences the level of discipline among the alumni while in higher learning institutions. The second objective was to explore the influence of participating in the national service programme on students' attitudes in higher learning education towards constructive feedback. The third objective was to assess the impact of participating in national service on the ability of alumni to make informed decisions on occupational choices. Snowball sampling technique was used to collect data from as many participants as possible. A sample of 1843 Emirati university students who are alumni of the national service programme, 106 parents of university national service students and 106 university lecturers, were recruited to participate in the study. A questionnaire, including closed-ended questions to collect quantitative data and open-ended questions to collect qualitative data, was used. The collected data were analysed using statistical analysis and thematic analysis. Before conducting analysis to address the specific objectives, a descriptive approach using frequency distributions, percentages and graphical representation were used to analyse demographic data and all the quantitative data. Another pre-test for objectives analysis conducted was Cronbach’s alpha test for reliability and validity of internal consistency, which showed significant reliability and validity of the data for further analysis. Pearson’s Product-Moment Correlation and Multiple Linear regression models were used to analyse the data in order to address the research objectives. The results showed that soft skills and behavioural maturity learnt during national service improve students discipline level, attitudes towards constructive feedback and the ability to make informed decisions as well as on academic development. The results also showed a significant relationship between improved discipline and commitment to academic studies and other responsibilities. The findings have concluded that participation in the national service programme equips young people with experiential and learning skills as well as behavioural maturity improvement that significantly influence their discipline level, academic development, attitudes towards constructive feedback and informed decision-making process. Therefore, the research recommends that the government should establish a diploma or degree programme for national service programme to increase its academic and career development scope.